"Food Deserts" in Urban Districts: Evidence from a Transitional Market and Implications for Macromarketing. (September 2016) - Cerovečki, Irena Guszak; Grünhagen, Marko
While the marketing literature has investigated the availability and affordability of food and food stores from various angles and in many different global contexts, a recent phenomenon that has only received scant attention in the marketing literature thus far is the appearance of food deserts in urban environments. Food deserts have been observed in Western markets (e.g., in the U.K. and the U.S.) with a literature base that originates in urban planning. This article represents the first attempt to introduce the food desert phenomenon to the marketing literature overall, and to the macromarketing context specifically. A definition of a food desert is created from a marketing perspective. The impact of emerging food deserts on market segments of vulnerable consumers, such as the elderly or mobility-impaired consumers, and the ensuing public policy implications appear particularly relevant to macromarketers. This study investigates the absence of food-sources in a context that may not appear as a likely candidate for this phenomenon, a transitional economy in Southeastern Europe, Croatia. Evidence for the existence of a food desert is provided through primary and secondary data, and public policy implications are discussed.